Regulation of Ras Signaling by S-Nitrosylation - Sónia Simão; Rafaela Ribeiro Agostinho; Antonio Martínez-Ruiz; Inês Maria Araújo (MDPI AG, 2023)
Ras are a family of small GTPases that function as signal transduction mediators and are involved in cell proliferation, migration, differentiation and survival. The significance of Ras is further evidenced by the fact that Ras genes are among the most mutated oncogenes in different types of cancers. After translation, Ras proteins can be targets of post-translational modifications (PTM), which can alter the intracellular dynamics of the protein. In this review, we will focus on how S-nitrosylation of Ras affects the way these proteins interact with membranes, its cellular localization, and its activity. S-Nitrosylation occurs when a nitrosyl moiety of nitric oxide (NO) is covalently attached to a thiol group of a cysteine residue in a target protein. In Ras, the conserved Cys118 is the most surface-exposed Cys and the preferable residue for NO action, leading to the initiation of transduction events. Ras transduces the mitogen-activated protein kinases (MAPK), the phosphoinositide-3 kinase (PI3K) and the RalGEF cellular pathways. S-Nitrosylation of elements of the RalGEF cascade remains to be identified. On the contrary, it is well established that several components of the MAPK and PI3K pathways, as well as different proteins associated with these cascades, can be modified by S-nitrosylation. Overall, this review presents a better understanding of Ras S-nitrosylation, increasing the knowledge on the dynamics of these proteins in the presence of NO and the underlying implications in cellular signaling.